2009
DOI: 10.1248/jhs.55.910
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Acid Fibroblast Growth Factor, Granulocyte Colony-stimulating Factor and Zinc Sulphate Accelerates Diabetic Ulcer Healing

Abstract: Our previous studies demonstrated that topic application of recombinant human acid fibroblast growth factor (aFGF) significantly, but still not completely, improved in diabetic ulcer healing. To obtain a maximal therapy for diabetic ulcer healing, a combined protocol containing aFGF, anti-oxidative reagent zinc (Zn) and stem cell stimulator granulocyte colony-stimulating factor (G-CSF), i.e.: aFGF/G-CSF/zinc sulphate (ZnSO 4 ), was explored in the present study. Diabetes was induced by a single dose of strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
1
0
3
Order By: Relevance
“… 161 As the main component of metalloproteinase, Zn can participate in the formation of ECM and promote wound healing. 162 Li et al constructed a ZnO/Ag/PVP/PCL nanofiber to enhance tissue regeneration and wound healing, and found that this composite structure had better anti-inflammatory, antibacterial, skin regeneration and wound healing effects than traditional drugs or single metal nanofibers. 163 In addition to ZnO, TiO 2 , CeO 2 , Fe 2 O 3 and other emerging nanoparticles also play a certain role in skin wound healing.…”
Section: Effects Of Nanoparticles On Wound Healingmentioning
confidence: 99%
“… 161 As the main component of metalloproteinase, Zn can participate in the formation of ECM and promote wound healing. 162 Li et al constructed a ZnO/Ag/PVP/PCL nanofiber to enhance tissue regeneration and wound healing, and found that this composite structure had better anti-inflammatory, antibacterial, skin regeneration and wound healing effects than traditional drugs or single metal nanofibers. 163 In addition to ZnO, TiO 2 , CeO 2 , Fe 2 O 3 and other emerging nanoparticles also play a certain role in skin wound healing.…”
Section: Effects Of Nanoparticles On Wound Healingmentioning
confidence: 99%
“…(9) Posteriormente, diversos autores comenzaron a utilizar factor de crecimiento estimulante de colonias de granulocitos (G-CSF), primero en modelo animal y luego en pacientes con pie diabético infectado. (10)(11)(12)(13)(14)(15) El G-CSF, al igual que el GM-CSF, es un factor endógeno hematopoyético movilizador de células madre y progenitores hematopoyéticos de la médula ósea hacia la sangre periférica, los cuales pueden ser cuantificados mediante la determinación de células CD34+ en sangre periférica. (10,12) A nivel sistémico actúa regulando la supervivencia, proliferación y diferenciación terminal de las células precursoras de neutrófilos desde la médula a la sangre.…”
Section: Introductionunclassified
“…A su vez, estimula la función de neutrófilos maduros favoreciendo la quimiotaxis de éstos y mejorando su capacidad fagocítica. (10,12,17) Por otro lado, induce la proliferación de células endoteliales promoviendo la angiogénesis. (10) La eficacia del G-CSF ha sido evaluada en varios ensayos clínicos en pie diabético infectado, observándose mejoría en los parámetros de infección, así como disminución en la incidencia de amputación y de estadía hospitalaria en estos pacientes.…”
Section: Introductionunclassified
See 1 more Smart Citation